The effect of using automatic mask dispenser on the contamination of surgical masks in the operating room - Pegah Abasian; Aygineh Hayrabedian; Mohammad Javad Tarrahi; Ahmad Ghadami (Tehran University of Medical Sciences, 2022)
Background & Aim: Hand disinfection methods are not germ-free, and infected hands transmit the infection. One of the personal protective equipment of the operating room is the mask, which will probably be contaminated by the hands when removing the mask. The aim of this study is to determine the effect of using automatic mask dispenser on the contamination of surgical masks in the operating room. Methods & Materials: The present study is a field experiment that was conducted on 120 hospital staff in Isfahan in 2021. The subjects were randomly divided into two groups of 60; automatic device and manual mask removal. The effect of contact of hands impregnated with fluorescent powder was measured during the removal of the mask in each group. The contamination area of ​​the removed mask and the lower mask on the back and front surfaces were compared in the two groups. Results: The Mann-Whitney test showed that there was a significant difference in the area impregnated with fluorescent powder from hand contact with the mask surface between the two methods (P<0.05). Only 125.6±77.8 mm2 of from the front surface and 30.6±26.0 mm2 from the back surface of the mask removed with the automatic mask dispenser were contaminated, while the ratio in the hand-removed mask was respectively 961.6±612.9 and 440.4±315.6 mm2. Conclusion: The study showed that eliminating hand contact with the body of the mask using an automatic mask dispenser, can reduce its contamination. Therefore, mechanization of services is effective in ensuring the safety of individuals' health and reducing costs. Clinical trial registry: IRCT20150715023216N11